PRMT1-rich exosomes derived from M2 macrophages as novel therapeutics for enhancing fracture healing - Haifeng Hong; Cuiyun Zhou; Haibing Wang; Changhui Lin; Min Fang; Juntian Liu; Minhui Yang (Tissue and Cell, 2026)

An Enzymatic Recombinase Amplification Coupled Lateral Flow Assay for Rapid, Visual, and Cost-Effective Detection of Bordetella pertussis - Piaoting Wen; Jian Liu; Mingqi Jiao; Hangxi Liu; Mei Lin; Sheping Zhang; Jun He; Ziyi Li; Changhui Xiao; Zhongliang Deng (Current Microbiology, 2026)

Depleting SfCarE: Innovative strategies for enhancing chlorantraniliprole toxicity through mixing with carbaryl in Spodoptera frugiperda (Lepidoptera: Noctuidae) - Qinqin Wang; Lin Zhou; Li Wang; Xiangshuai Li; Pei Liang; Changhui Rui; Huizhu Yuan; Li Cui (Pesticide Biochemistry and Physiology, 2026)

Microbial mechanisms underlying differences of methane emissions between urban and rural wetlands - Yuwen Lin; Xinyu Yi; Chen Ning; Yong Li; Yinghe Peng; Shuguang Liu; Changhui Peng; Xiaoyong Chen; Shuailong Feng; Pengpeng Duan; Yan Liu; Juyang Liao (Soil Biology and Biochemistry, 2026)

Structure-function modulation of sodium caseinate: Insights from non-covalent reuterin binding - Mao-Cheng Sun; Jie-Ting Wang; Ying-Di Wang; Lin-Yu Hu; Shi-Qi Yu; Tiehua Zhang; Changhui Zhao (Food Chemistry, 2025)

The association between maternal exposure to ten neonicotinoid insecticides and preterm birth in Guangxi, China - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Xiaogang Wang; Qian Liao; Lidi Lei; Shun Liu; Dongping Huang; Xiaoqiang Qiu; Xiaoyun Zeng (Environmental Pollution, 2025)

Effects of neonicotinoid pesticide exposure in the first trimester on gestational diabetes mellitus based on interpretable machine learning - Dongxiang Pan; Lihong Zhou; Changhui Mu; Mengrui Lin; Yonghong Sheng; Yang Xu; Dongping Huang; Shun Liu; Xiaoyun Zeng; Virasakdi Chongsuvivatwong; Xiaoqiang Qiu (Environmental Research, 2025)

Novel Cu(I)/Cu(II) oxide nanowires electrode with efficient cyclic catalytic performance for electroreduction of nitrate wastewater to ammonia - Ye Du; Wenjie Liu; Changhui Zhou; Chaoyue Xie; Zhinan Dai; Jie Wang; Jia Lin; Jinhua Li; Hong Zhu; Jing Bai; Baoxue Zhou (Journal of Environmental Chemical Engineering, 2024)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

Cross-sectional rainfall observation on the central-western Tibetan Plateau in the warm season: System design and preliminary results - Kun Yang; Yingying Chen; Lazhu; Changhui Zhan; Xiaoyan Ling; Xu Zhou; Yaozhi Jiang; Xiangnan Yao; Hui Lu; Xiaogang Ma; Lin Ouyang; Weihao Pan; et al. (Science China Earth Sciences, 2023)

A bi-objective optimization for integrated truck operation and storage allocation considering traffic congestion in container terminals - Yi Tao; Shiling Zhang; Changhui Lin; Xiaofan Lai (Ocean & Coastal Management, 2023)

Local community assembly processes shape β‐diversity of soil phoD ‐harbouring communities in the Northern Hemisphere steppes - Lin Xu; Nianpeng He; Xiangzhen Li; Huili Cao; Chaonan Li; Ruili Wang; Changhui Wang; Minjie Yao; Shungui Zhou; Junming Wang (Global Ecology and Biogeography, 2021)
Aim The contemporary coexistence theory suggests that species pool, environmental filtering, dispersal assembly processes, ecological drift and biotic interactions collectively determine the β‐diversity of communities. However, we know little about the biogeographical patterns of the β‐diversity of microbial communities harbouring the alkaline phosphatase phoD gene ( phoD communities, hereafter) and whether these mechanisms are all‐important in shaping phoD communities’ β‐diversity in natural steppe ecosystems. Location Northern Hemisphere steppes. Time period July to August 2018. Major taxa studied Alkaline phosphatase ( phoD gene) encoding community. Methods Using the high throughput amplicon sequencing method, soil phoD communities were comparatively studied along three representative regions of the Northern Hemisphere steppes, namely the Qinghai‐Tibetan Plateau, Inner Mongolian Plateau and the Loess Plateau. Each region harbours three types of steppes (habitats): meadow, typical and desert steppes. Results We observed significantly higher phoD β‐diversity in the Qinghai‐Tibetan than in the Loess and Inner Mongolian Plateaus and significantly lower β‐diversity in the typical steppes than in other steppe types. The decay rates of phoD β‐diversity with geographical distance varied in different steppe regions and types. The phoD β‐diversity was not significantly influenced by species pool; instead, environmental filtering, dispersal assembly processes, ecological drift and biotic interactions jointly shaped the β‐diversity patterns. The β‐deviation variations (β‐diversity excluding the effects of species pool) were influenced by spatial and environmental factors and biotic interactions, among which soil pH was the key environmental determinant. The soil pH driving β‐diversity mechanism was steppe region and habitat specific. Main conclusions The biogeographical patterns of phoD β‐diversity were mainly driven by local community assembly processes in the Northern Hemisphere steppes.

Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Lin Jiang; Huai Chen; Qiuan Zhu; Yanzheng Yang; Mingxu Li; Changhui Peng; Dan Zhu; Yixin He (Journal of Soils and Sediments, 2019)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Qiuan Zhu; Changhui Peng; Philippe Ciais; Hong Jiang; Jinxun Liu; Philippe Bousquet; Shiqin Li; Jie Chang; Xiuqin Fang; Xiaolu Zhou; Huai Chen; Shirong Liu; et al. (Global Change Biology, 2017)
Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Modeling and Manufacturing Technology for Personalized Biological Fixed Implants - Zhang Guoqing; Yang Yongqiang; Lin Hui; Song Changhui; Xiao Ran; Yu Jiakuo (Journal of Medical and Biological Engineering, 2017)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Zhen’an Yang; Wan Xiong; Yingyi Xu; Lin Jiang; Erxiong Zhu; Wei Zhan; Yixin He; Dan Zhu; Qiuan Zhu; Changhui Peng; Huai Chen (Environmental Monitoring and Assessment, 2016)

Soil Carbon Dioxide Fluxes from Three Forest Types of the Tropical Montane Rainforest on Hainan Island, China - Xinhua Jiang; Huai Chen; Changhui Peng; Yide Li; Yixin He; Dexiang Chen; Mingxian Lin; Ji Hu; Tianli Ma; Liangfeng Liu; Xinwei Liu; Miao Xia; et al. (Water, Air, & Soil Pollution, 2016)